Aggregation-induced emission of siloles. Issue 10 (14th October 2015) - Zhao, Zujin; He, Bairong; Tang, Ben Zhong
<x xml:space="preserve">Abstract</x> Recent advances in the structure–property relationship decipherment and luminescent functional materials development of AIE-active siloles are reviewed.